Winner of the CAML Student Paper Award 2012: The Plexure of Copyright Infringement - McKibbon, Richard (CAML Review / Revue de l’ACBM, 2012)
This paper reflects on copyright law as it relates to musical works by examining a work entitled Plexure by the Canadian composer John Oswald that is made up entirely of unlicensed samples from other works. While the recording industry views works like Oswald’s to be infringing on copyright, this paper argues that these types of transformative works should be allowed under the fair use, or fair dealing, provisions of copyright law, and that to disallow them ultimately stifles creativity and the advancement of culture in general. The paper argues that there needs to be an expansion of the current fair use laws to include a broader interpretation of works of transformative appropriation like Oswald’s Plexure.